The effect of compensation and job satisfaction towards job performance among employees in Employees Provident Fund (EPF) Kuala Terengganu Darul Iman / Nurul Fatin Abdullah - Abdullah, Nurul Fatin (2014)
This study attempted to identify the effect of compensation towards employee job performance and to determine the relationship between job satisfaction and job performance among employees in Employees Provident Fund (EPF) Kuala Terengganu, Terengganu. 50 questionnaires were personally distributed to respondents, which were employees in Employees Provident Fund (EPF) Kuala Terengganu, Terengganu. After the questionnaire was completed, it was collected by researcher which is the amount of questionnaire collected is 45 and five questionnaires were unusable and rejected due to incomplete answers in the questionnaires. This study was significant because it investigate the effect of the compensation toward employee job performance and determine the relationship between job satisfaction and job performance among employees in Employees Provident Fund (EPF) Kuala Terengganu, Terengganu.